Entre acordes, cenas e amorosidades: a educação humanizadora em um Centro de Referência da Pessoa Idosa para a promoção do envelhecimento com qualidade de vida - Isamara Grazielle Martins Coura (2021)
According to the Brazilian Institute of Geography and Statistics (Instituto Brasileiro de Geografia e Estatística - IBGE), the country's demographic scenario indicates that its population is aging. IBGE data published in 2019 indicate that 13% of Brazil's population is composed of elderly people, which comprises 28 million people in this age group. IBGE also points out that in 2050 Brazil will have practically one third of the Brazilian population made up of people over 60 years old. Given this, it is important that those people live with quality of life, in order to have an increasingly healthy aging and conditions to be and feel socially active. Therefore, it is necessary to offer, especially through public policies, places and conditions that allow the involvement of these citizens in different environments, as well as provide adequate eldercare. They also should be provided with opportunities for their continuous learning, aiming at a greater understanding of their social role, their rights and how to live this stage of life better. This work presents a doctoral-level study whose main purpose is to verify if the educational practices offered at the Vereador Sérgio Ferrara Senior Reference Center contribute to improving the quality of life of people aged 60 and over. The analysis is based on the “Theater” and the “Voice and Guitar” classes. These study objectives are to verify how the elderly perceive the educational practices that are offered to them, what are their motivations for attending them and to analyze what benefits they have been obtaining in terms of quality of life. The research also seeks to analyze the profile of the teachers involved in the chosen activities, to investigate how they are trained and how they understand the education for the elderly. This is a qualitative research study which used methods such as participant observation and semistructured interviews for data collection. The observations were made face-to-face between February 2019 and February 2020 and virtually between June and October 2020, due to the COVID-19 pandemic. In total, nine people were interviewed: two teachers; the CRPI coordinator and six elderly people. From the group of seniors, four of them were women and two were men, all aged between sixty-seven and ninety-five years old. The results point to an improvement in the quality of life of the elderly as a consequence of their participation in the analyzed activities. The benefits generated refer to greater social integration and greater selfworth, as well as improvements in their health, for example, in relation to memory. The findings of this study also reveal the importance of affectionate and respectful treatment by teachers in order to have positive results in these educational processes. Regarding the teachers’ training, it is possible to say that they learn in the course of their pedagogical work with the elderly. In addition, the research revealed the importance of these types of activities to minimize the negative effects of the COVID-19 pandemic on the quality of life of these subjects.